Studi Kimia Adi (Fine Chemical) Industri Antibiotika - Hayat S (Balai Besar Kimia dan Kemasan, 1987)
Antibiotic have been know since 1929 by Fleming. According to Fleming antibiotic is a potential subtance namely Penicilline. Antibiotic is a subtance because grew by mold or a special bacteria or made by of a Subtance use semi Synthesa/Synthesa methode, who is inhibit of other grown micro organisme beside result of this self micro organisme. Indonesia still import Antibiotic raw material namely : Penicillin salt and derivat's, Streptomycine salt and derivat's Tetracycline salt and derivat's, Chloramphenicol salt and derivat's, Erythrornycine salt and derivat's. Indonesia has been imported 12 I, l 05 Kg and 13 7 ,641 Kg Testracycline salt in 1984 and 1985. This type is the most quantity import.